2005
DOI: 10.1016/j.jacc.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The Adequacy of Laboratory Monitoring in Patients Treated With Spironolactone for Congestive Heart Failure

Abstract: Many patients treated with spironolactone for CHF do not receive needed follow-up of potassium or creatinine concentrations, although hyperkalemia and renal dysfunction are common. Elevated baseline creatinine predicts patients at high risk. Physician education of the risks of spironolactone and the need for follow-up is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 9 publications
(7 reference statements)
2
79
2
3
Order By: Relevance
“…In the present study, the renal function worsening was more prevalent in the group treated with spironolactone, despite the low incidence of hyperkalemia (2%) 3 . Although it is expected an increase in the incidence of hyperkalemia with the current treatment of HF due to the use of angiotensinconverting enzyme inhibitor (ACEI) and spironolactone, its actual frequency is not well known and can vary according to the disease severity and presentation.…”
Section: Introductioncontrasting
confidence: 50%
See 2 more Smart Citations
“…In the present study, the renal function worsening was more prevalent in the group treated with spironolactone, despite the low incidence of hyperkalemia (2%) 3 . Although it is expected an increase in the incidence of hyperkalemia with the current treatment of HF due to the use of angiotensinconverting enzyme inhibitor (ACEI) and spironolactone, its actual frequency is not well known and can vary according to the disease severity and presentation.…”
Section: Introductioncontrasting
confidence: 50%
“…Due to the increased number of spironolactone prescriptions for heart failure (HF) verified after the RALES 1 study demonstrated a reduction of 30% in mortality, there was an increase in the hospitalizations due to hyperkalemia 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many studies exclude patients with high baseline serum potassium concentrations or severely impaired renal functionsubgroups expected a priori to be at an increased risk of hyperkalemia (54). Moreover, screening of electrolyte levels in clinical trials is more rigorous than in clinical practice (55,56), and thus occurrences of hyperkalemia are more likely to be reported and appropriately managed with changes to the patient's regimen or diet. However, regular monitoring of serum electrolyte levels in clinical practice should be sufficient to detect any changes in potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Risks of hyperkalemia and worsening renal function often limit use of MRA therapy in patients with heart failure 12, 13, 14. Several factors increase hyperkalemia risk, including renal insufficiency and diabetes mellitus 15, 16, 17, 18, 19. Although the presence of renal insufficiency or diabetes mellitus increases the risk of adverse events with MRA therapy in heart failure, these drugs are potentially beneficial in these higher‐risk populations.…”
Section: Introductionmentioning
confidence: 99%